Parent-couple satisfaction, parent depression, and child mental health in families with autistic children - Piro-Gambetti, Brianna; Greenlee, Jessica; Bolt, Daniel; Papp, Lauren M.; Hartley, Sigan L. (Frontiers in Psychiatry, 2024)
Introduction: Within two-parent households, the parent-couple subsystem (marital or romantic partner relationship) is posited to shape the mental health of both parents and children. Autistic children and their parents have an elevated-risk for mental health problems. The present study longitudinally examined the mediating role of the quality of the parent-couple relationship in timeordered pathways between changes in the mental health problems of autistic children and in parent depression symptoms at a within-family level.Using four time points of data collected on 188 families of autistic children (aged 5-12 years) across 3 years, the bidirectional associations between parent-couple relationship satisfaction, parent depressive symptoms, and child internalizing and externalizing mental health problems were investigated. Two multi-group (grouped by parent gender) complete longitudinal mediation models in structural equation modeling using Mplus software were conducted.Results: Parent-couple relationship satisfaction mediated: 1) the association between higher parent depressive symptoms and higher child internalizing mental health problems 12 months later for both mothers and fathers, and 2) the association between higher child externalizing mental health problems and higher father depression symptoms 12 months later. Father depression symptoms mediated a pathway from lower parent-couple satisfaction to higher child internalizing mental health problems 12 months later, and mother depression symptoms mediated the pathway from higher child externalizing mental health problems to lower parent-couple satisfaction 12 months later.Findings highlight the bidirectional and complex ways that parent and child mental health and the quality of the parent-couple relationship are entwined across time in families of autistic children. Family-wide interventions that address the needs of multiple family members and family systems are best suited to improve the mental health of parents and autistic children.